Paolo Mantegazza - Chiarelli, Cosimo (Firenze University Press, 2002)
The book presents a selection of the works presented during various encounters held in sites connected with the life of Paolo Mantegazza, aimed at retrieving and valorising his cultural legacy. An eclectic figure - scientist, novelist, anthropologist and politician - Paolo Mantegazza (1831-1910) played a leading role in Italian society and the cultural scene of the late nineteenth century. The contributions of academics from different disciplines enable us to reconstruct both the great variety of the man's interests and curiosities, and the strict methodological rigour that guided his entire scientific production and is today the most evident sign of his contemporary relevance.